Iš cinkografijų istorijos Lietuvoje - Juodakis, Virgilijus (Knygotyra, 1973)
In Vilnius zincography appeared twenty years earlier than in Kaunas.S. Fleury (in 1904) and A. Jurašaitis (in 1905) were the first to make zincographic clishes in Vilnius. This was effected in their own photography studies where at the same time they made photoes. Both died in 1915.In Kaunas zincography appeared only in 1923. The firms „Ostra“ (later „Žaibas“) and „Grafika“ were established specially for this purpose. The firms engaged foreign specialists from Germany, Austria and Latvia.Development of zincography conditioned the appearance of well illustrated publications.